Implementation Of Motorcycle Rental Agreement - Adjie, Habib; Sinaga, Erdiana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The lease purchase agreement is a new type of agreement that arises in the community. As with the new type of agreement, leasing in Indonesia has not been regulated in the several definitions put forward by the legal experts above and also in the decree of the Minister of Trade and Cooperatives, there is no uniformity. However, if you pay attention, it can be concluded that the lease-purchase agreement is more likely to lead or lead to the form of a sale-purchase agreement, rather than a lease. Because in the lease purchase agreement, the transfer of property rights is the main point. So the purpose of leasing is to sell goods, not to rent or become tenants of goods. In the event that the tenant defaults in the lease purchase agreement, the tenant is fully responsible for the risk. This is in accordance with the contents of the lease-purchase agreement that has been agreed between the two parties. For the problem of resolving disputes in the motor vehicle rental agreement in practice, it can be reached in two ways, namely through deliberation and consensus and through a lawsuit in court. Court is the last resort taken by the dealer, if the tenant really does not want to be responsible for all his mistakes, namely with the intention of transferring the motor vehicle which is the object of the lease purchase agreement.